The orphic poem about stones ("Lithica") - Tatiana Alexandrova (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The paper represents a literary translation of the late ancient poem “Lithica” (“On stones”). Scholars date the poem by the period from 2nd to 4th centuries. Along with the “Orphic Argonautica” the “Litica” is a part of the Orphic corpus. From the point of view of the genre it is a lapidary in verse (a literary work about stones, mostly precious and unusual). Lapidaries were very popular in the epoch of late antiquity and Middle age. The author of the “Litica” borrows his knowledge from different sources; his work has intersections with the works of Theophrastus, Pliny the Elder, Galenus, Dioscorides and with the prosaic lapidaries of different times. Stories about the stones are located into the double narrative frame: these is a bucolic plot, in which the narrator on the way to the temple meets the “divine man” Theodamas who tells him about some stones. In the middle of the narration Theodamas inserts in his own story the one of the diviner Helenus (this fact should be evidence of the deep antiquity of the information given in the poem). The main content of the poem is information about approximately 30 different minerals, their useful proprieties as therapeutic, so magic; in the commentaries are given the modern hypotheses of their identification. The information about the stones in the poem is given unevenly; from the simple mention up to the detailed story including medical or magic recipes and mythological digressions connected with the origin of each stone. As well as the “Orphic Argonautica” the ”Litica” reflects the decline of ancient rationalism and the domination of the religious interests over the “scientific” ones which is typical for the late ancient mentality.